Reducing Energy Costs for Gas Preheating through Gas-Dynamic Stratification in the Leontiev Tube - Kovalnogov V.N.; Rudnik R.S.; Matveev A.F. (Problems of the Regional Energetics, 2025)
The main objectives of this study are to reduce the energy consumption for gas preheating and improve the efficiency of compression systems using gas-dynamic temperature stratification in the Leontiev tube. In order to achieve these objectives, the following tasks were carried out: a numerical analysis was performed using the finite volume method (RANS) and the k–ω SST tur-bulence model, and the Navier–Stokes equations were discretized on a multi-block mesh of 3 million cells, with local refinement in the nozzle and separation wall zones. Particular attention was paid to the influence of the inlet nozzle geometry on the temperature distribution, flow ve-locity, and heat transfer through the separation wall, as well as the stability of the flow under different pressure differentials. The most significant results include the superior performance of the bell-shaped nozzle design over the annular one: modelling showed a 60 K temperature dif-ference between supersonic and subsonic flows (110.5% higher than the baseline), a 20–25 K increase in hot flow temperature at the outlet, stable flow without pressure surges, and effective gas heating prior to throttling using pipeline pressure drops, preventing condensation and reduc-ing costs. The significance of these results lies in demonstrating the superiority of machine-free energy separation technologies, such as gas-dynamic stratification in the Leontiev tube with a bell-shaped nozzle, over traditional energy-intensive heating methods, leading to more rational resource utilization and reduced environmental impact under strict energy efficiency and ecolog-ical standards.